Urartian seals with an image of a stela - Yengibaryan, Nora (ARAMAZD: Armenian Journal of Near Eastern Studies, 2017)
Among the graphic compositions of a small group of frustum-shaped Urartian seals with a hanging eye are the images of stelae with a rounded top and a surface divided by multi-row horizontal lines. These stelae were fixed in the ground or high pedestal. Seals with these described images were discovered during the excavations of a necropolis near Karchaghbyur village of the Republic of Armenia (in the Sevan lake basin) and the site of Karmir Blur (the Urartian town Teišebaini). These were also found accidentally in Eastern Turkey. A well-known stamp from Toprakkale has a similar type of depiction.